Hubungan Pengetahuan, Norma Subjektif dan Persepsi Kontrol Perilaku dengan Niat Ibu Rumah Tangga Berisiko HIV dalam Mengakses Layanan VCT - Bella Risca Monica; Bagoes Widjanarko; Priyadi Nugraha Prabamurti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Until now there has not been found a cure for HIV / AIDS, but the number of cases continues to increase. In Semarang City, according to the type of work of HIV / AIDS cases in housewives occupies the second position which will have an impact on increasing perinatal risk from mother to child. So prevention efforts need to be done early on through the VCT (Voluntary Counseling and Testing) program for housewives at risk of HIV.The purpose of this study is to analyze the related between knowledge, subjective norms and perceptions of behavioral control with the intentions of HIV risk housewives to accessing VCT (Voluntary Counseling and Testing) services in the Bandarharjo, Semarang City. This type of research is observational with cross-sectional approach. This study population housewives at risk of HIV who still have a husband. Inclusion criteria are housewives aged 20 - 49 years who have been exposed to information about HIV / AIDS. The size of the study sample was 91 respondents with proportional random sampling technique. This study uses univariate and bivariate analysis using the Chi Square test. The study has passed the ethics test from the Health Research Ethics Commission of the Faculty of Public Health, University of Diponegoro under number 190 / EA / KEPK-FKM / 2019.The results showed that knowledge (p = 0.043), subjective norms (p = 0.017), and perceived behavioral control (p = 0.000) were related to the intention of HIV risk housewives to accessing VCT services. It is expected that the Bandarharjo Public Health Center will increase public awareness about the importance of VCT and conduct outreach with mobile VCT. In addition, there is still a need for an active role of health cadres in efforts to tackle HIV / AIDS in their neighborhoods.